Parent rating of executive function in fetal alcohol spectrum disorder: A review of the literature and new data on Aboriginal Canadian children. Issue 6 (18th August 2017) - Rai, Jaspreet K.; Abecassis, Maurissa; Casey, Joseph E.; Flaro, Lloyd; Erdodi, Laszlo A.; Roth, Robert M.
ABSTRACT: Aboriginal children in Canada are at high risk of fetal alcohol spectrum disorder (FASD) but there is little research on the cognitive impact of prenatal alcohol exposure (PAE) in this population. This paper reviews the literature on parent report of executive functioning in children with FASD that used the Behavior Rating Inventory of Executive Function (BRIEF). New data on the BRIEF is then reported in a sample of 52 Aboriginal Canadian children with FASD for whom a primary caregiver completed the BRIEF. The children also completed a battery of neuropsychological tests. The results reveal mean scores in the impaired range for all three BRIEF index scores and seven of the eight scales, with the greatest difficulties found on the Working Memory, Inhibit and Shift scales. The majority of the children were reported as impaired on the index scores and scales, with Working Memory being most commonly impaired scale. On the performance-based tests, Trails B and Letter Fluency are most often reported as impaired, though the prevalence of impairment is greater for parent ratings than test performance. No gender difference is noted for the parent report, but the boys had slightly slower intellectual functioning and were more perseverative than the girls on testing. The presence of psychiatric comorbidity is unrelated to either BRIEF or test scores. These findings are generally consistent with prior studies indicating that parents observe considerable executive dysfunction in children with FASD, and that children with FASD may have more difficulty with executive functions in everyday life than is detected by laboratory-based tests alone.